Exploration and Validation of Immune and Therapeutic-Related Hub Genes in Aortic Valve Calcification and Carotid Atherosclerosis - Wei K; Cao Y; Kong X; Liu C; Gu X (Dove Medical Press, 2024)
KaiMing Wei,1,2,* Yuan Cao,1,3,* XiangJin Kong,1,2 ChuanZhen Liu,1,2 XingHua Gu1,2 1Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People's Republic of China; 2Department of Cardiovascular Surgery, Qilu Hospital of Shandong University, Jinan, Shandong, People's Republic of China; 3National Key Laboratory for Innovation and Transformation of Luobing Theory; The Key Laboratory of Cardiovascular Remodeling and Function Research, Chinese Ministry of Education, Chinese National Health Commission and Chinese Academy of Medical Sciences; Department of Cardiology, Qilu Hospital of Shandong University, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: XingHua Gu, Email guxinghua@email.sdu.edu.cnBackground: Cardiovascular diseases, such as aortic valve calcification (AVC) and carotid atherosclerosis (CAS), impose substantial health challenges on a global scale. Both disorders have overlapping risk factors, which might trigger similar immune-inflammatory reactions in both diseases.Methods: Shared differentially expressed genes (DEGs) were identified in the AVC and CAS datasets from the Gene Expression Omnibus (GEO). Candidate hub genes associated with immunity were identified using LASSO and immune cell infiltration analysis, and single gene set enrichment analysis (GSEA) was performed on the datasets. Subsequently, the hub genes were confirmed by qRT‒PCR validation in tissue samples.Results: A total of 140 upregulated and 65 downregulated common genes were screened. Enrichment analyses highlighted immune system processes, response to stress, and cytokine pathways among the identified CEGs. LASSO identified candidate hub genes, including ANGPTL1, CX3CR1, and CCL4. Immune cell infiltration analysis emphasized the participation of immune cells, including macrophages, γδ T cells, and resting NK cells. The three hub genes were validated by qRT‒PCR analysis.Conclusion: Our study explored immunological processes, including immune-related genes and cells, involved in the development of AVC and CAS. In particular, the identified hub genes ANGPTL1, CX3CR1, and CCL4 play crucial roles in mediating immune-inflammatory responses, which are central to the pathogenesis of these cardiovascular diseases, and the involvement of these genes in key immune pathways suggests that they could serve as potential biomarkers for early diagnosis or as targets for therapeutic strategies.Keywords: aortic valve calcification, carotid atherosclerosis, immune-related genes